Perancangan Buku Cerita Interaktif Mengenal Dan Mengelola Sampah Untuk Anak Golden Age - Febriyanti, Sarah; Putra, Bramanta Octa Danu (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2023)
The waste problem in Indonesia has yet to find a significant solution. The utilisation of waste in usable goods can have an impact on the environment, and needs to be improved in providing appeals in the form of education to children aged from an early age, namely, at the age of 3-6 years which is a golden age child. In this case it is necessary to make an educational media about the initial introduction to waste as well as the 3 types of waste groups accompanied by how to manage waste with methods that are easy to understand in a simple visual form. Educational media in the form of interactive storybooks that are useful for building the character of children who care about waste by utilising their sensory and sensory functions. The research was conducted by means of observation, documentation and material study to find out directly the habits of the research target in disposing and managing waste. The fact is that many children and parents still do not care or do not know more about waste, its categories and how to manage it. Therefore, this interactive storybook is very necessary for the initial media of children's education by making parents as the intermediary media.